Urban Street Space after Covid-19: (Indicators of safe and healthy urban street space) - et. al., Sajidah Kazim Aliwi Al-Kindi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Restrictions on the movement of people and the social distancing in public urban spaces are among the main measures taken to limit the spread of Covid-19 virus. The research focuses on these measures that led to a change in the urban space organization at the street level as well as the performance and characteristics of social and recreational activities to suit those changes at the level of urban spaces (open urban spaces and urban mobility), which prompted many countries of the world to think of new models for urban street space and its urban uses in healthy and sustainable ways. The research aims to shed light on the measures followed by some global countries with a focus on the cases of Italian cities - being the most affected than the rest of the European countries during the outbreak of the Corona epidemic in the year 2020. The research assumes that flexible and sustainable space organization has an effective role in accommodating new movement patterns and events, and achieving a safe and healthy environment, then the research reached the importance of sustainable mobility plans, and a rethinking of the way we move across the city and the way we use urban street space to form a flexible space organization that controls the volume of flows and rapid response to emergency developments, thus achieving better job performance and a safe and healthy environment.